Ghrelin‐insulin‐like growth factor‐1 axis is activated via autonomic neural circuits in the non‐alcoholic fatty liver disease. Issue 5 (27th January 2020) - Nagoya, Takuro; Kamimura, Kenya; Inoue, Ryosuke; Ko, Masayoshi; Owaki, Takashi; Niwa, Yusuke; Sakai, Norihiro; Setsu, Toru; Sakamaki, Akira; Yokoo, Takeshi; Kamimura, Hiroteru; Nakamura, Yuka; et al.
Abstract: Background: The correlation of the growth hormone (GH) and insulin‐like growth factor‐1 (IGF‐1) with non‐alcoholic fatty liver disease (NAFLD) has been reported in epidemiological studies. However, the mechanisms of molecular and inter‐organ systems that render these factors to influence on NAFLD have not been elucidated. In this study, we examined the induction of ghrelin which is the GH‐releasing hormone and IGF‐1, and involvement of autonomic neural circuits, in the pathogenesis of NAFLD. Methods: The expression of gastric and hypothalamic ghrelin, neural activation in the brain, and serum IGF‐1 were examined in NAFLD models of choline‐deficient defined l‐amino‐acid diet‐fed, melanocortin 4 receptor knockout mice, and partial hepatectomy mice with or without the blockades of autonomic nerves to test the contribution of neural circuits connecting the brain, liver, and stomach. Key Results: The fatty changes in the liver increased the expression of gastric ghrelin through the autonomic pathways which sends the neural signals to the arcuate nucleus in the hypothalamus through the afferent vagal nerve which reached the pituitary gland to release GH and then stimulate the IGF‐1 release from the liver. In addition, high levels of ghrelin expression in the arcuate nucleus were correlated with NAFLD progression regardless of the circuits. Conclusions: Our study demonstrated that the fatty liver stimulates the autonomic nervous signal circuits which suppress the progression of the disease by activating the gastric ghrelin expression, the neural signal transduction in the brain, and the release of IGF‐1 from the liver. Abstract : The neural signals from the liver with fatty infiltration activates the release of gastric ghrelin, leading to the activation of neural signals to the brain and release of IGF‐1 from the liver. The hypothalamic ghrelin may contribute to appetite.